Un « sport noir » ? - Nicolas Martin-Breteau (Transatlantica)
Basketball is today dominated by African-American players and is consequently considered as a black sport. Throughout the 20th century, vast numbers of African Americans became involved in this sport, to such an extent that African Americans have come to represent the great majority of NBA players. For more than a century, this athletic domination has given rise to heated controversies: most of the time it was explained using genetics (Blacks are athletically superior) or environmental theories (the poverty of urban Blacks leads them toward sports). However, one can see in this domination a political will to fight for equality, dignity, and recognition. Thus, whether it is celebrated by African Americans as a chance for racial uplift or criticized as a dangerous illusion, sport and basketball have been a central aspect of their political struggles.